Hemorrhagic Cystitis due to BK Reactivation in a Young Female Treated for Hodgkin-Disease - R. Le Calloch; J. C. Ianotto; C. Berthou; A. Tempescul (Case Reports in Hematology)
Hodgkin's lymphoma is a disease with a high rate of curability under classic chemo-radiotherapy regimes. Complications due to chemotherapy could include viral reactivation due to chronic lymphopenia. BK virus (BKV) is a polyoma virus belonging to the Papovaviridae family with antibody seroprevalences in healthy populations varying from 60% to 80%. Initial infections are asymptomatic usually occur in early childhood, after which the viruses remain latent in the kidneys or urothelium. Reactivation of BKV occurs in individuals with severe immunosuppression during HIV infections, transplantation or, exceptionally, after classical chemotherapy. BKV incidence is approximately 0% to 5% in immunocompetent individuals. Reactivation is associated with nephropathy and haemorrhagic cystitis. Herein, we present a case of a haemorrhagic cystitis due to BKV reactivation in a patient with Hodgkin's disease treated with chemotherapy.